2003
DOI: 10.1002/art.10783
|View full text |Cite
|
Sign up to set email alerts
|

Radiologic features in juvenile idiopathic arthritis: A first step in the development of a standardized assessment method

Abstract: Objective. To describe radiologic features of patients with juvenile idiopathic arthritis (JIA) in a standardized manner, to test the reliability and feasibility of this description, and to correlate these features with clinical signs as a first step in the development of a standardized assessment method.Methods. The placebo-controlled study of sulfasalazine in patients with oligoarticular, extended oligoarticular, and polyarticular JIA performed by the Dutch Juvenile Idiopathic Arthritis Study Group yielded t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
50
0
1

Year Published

2003
2003
2013
2013

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 79 publications
(54 citation statements)
references
References 26 publications
3
50
0
1
Order By: Relevance
“…), and 3) feasibility (Can the instrument be feasibly applied in the intended setting?). We confirmed, to some degree, the truth and feasibility of the Dijkstra score in a clinical trial setting in our previous study (9). In the current study, we focus on the discrimination criterion as it applies to the Dijkstra score.…”
supporting
confidence: 83%
See 4 more Smart Citations
“…), and 3) feasibility (Can the instrument be feasibly applied in the intended setting?). We confirmed, to some degree, the truth and feasibility of the Dijkstra score in a clinical trial setting in our previous study (9). In the current study, we focus on the discrimination criterion as it applies to the Dijkstra score.…”
supporting
confidence: 83%
“…In our previous study, we demonstrated that scores for swelling and osteopenia were only moderately reliable (9). Despite detectable change, we still believe that both swelling and osteopenia are of limited value in a scoring system.…”
Section: Discussionmentioning
confidence: 91%
See 3 more Smart Citations